2019
DOI: 10.1002/mp.13523
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of respiratory phase shifts on motion‐tracking accuracy of the CyberKnife Synchrony™ Respiratory Tracking System

Abstract: Purpose The SynchronyTM Respiratory Tracking System (SRTS) component of the CyberKnife® Robotic Radiosurgery System (Accuray, Inc., Sunnyvale CA) enables real‐time tracking of moving targets by modeling the correlation between the targets and external surrogate light‐emitting diode (LED) markers placed on the patient’s chest. Previous studies reported some cases with respiratory phase shifts between lung tumor and chest wall motions. In this study, the impacts of respiratory phase shifts on the motion‐tracking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 28 publications
3
22
1
Order By: Relevance
“…In addition, motion interplay and dose blurring effects were not observed with Synchrony enabled. The sensitivities of CK Synchrony to surrogate phase shifts reported in the literature 16 were not observed for the Radixact Synchrony system. This work provided evidence that Synchrony reduces effects of intrafraction respiratory motion that are not accounted for using the current, ITV‐based motion management strategy for helical tomotherapy plans.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…In addition, motion interplay and dose blurring effects were not observed with Synchrony enabled. The sensitivities of CK Synchrony to surrogate phase shifts reported in the literature 16 were not observed for the Radixact Synchrony system. This work provided evidence that Synchrony reduces effects of intrafraction respiratory motion that are not accounted for using the current, ITV‐based motion management strategy for helical tomotherapy plans.…”
Section: Resultsmentioning
confidence: 79%
“…For example, for similar tracking experiments on CK Synchrony, Akino et al . reported values of δ 95% to be as large as 2.8 mm for irregular respiratory motion with the surrogate and target in‐phase 16 and Inoue et al reported values of δ 95% ranging from 1.0 to 3.5 mm 25 . Akino et al found extremely large tracking errors when the surrogate and the target were out of phase, such as δ 95% >9 mm for a surrogate phase of +15% and δ 95% >6 mm for a surrogate phase of +10%.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…66,67 Across CyberKnife, Vero and MLC tracking lung SBRT treatment planning studies, planning target volume (PTV) reductions of 40-50% and corresponding reductions in mean lung dose have been demonstrated depending on the motion magnitude. 4,66,67,70,71 Corresponding clinical outcomes are yet to be demonstrated, however literature suggests ~2% reduction in toxicity per Gy reduction in mean lung dose. 72,73 MLC tracking may enable SBRT treatment for large lesions in the lung, as a reduction of the PTV with MLC tracking allows larger lesions to possess the same dose footprint as smaller lesions with an ITV expansion.…”
Section: Intra-fraction Correction For Motion Encompasses Inter-fractmentioning
confidence: 99%